A Fuzzy expert based multi-criteria performance appraisal model for police officers - Egessa, Bryan (Strathmore University, 2021)
Performance appraisals play a key role in management of human capital and in particular in determining the effectiveness of an employee and to map out their developmental needs. Subjective appraisals are prevalent especially in the public sector, which has contributed to bias and inconsistent ratings and lack of transparency in determining promotions and reward. The appraised employees therefore hardly expect benefits from the exercise other than organisational compliance with regulations. Effective performance appraisal should be void of bias with measurable outputs that can guide various human capital management procedures. The purpose of this research was to establish the gap in appraisal practices in policing organisations and to present a solution that would enhance objectivity in the appraisal of police officers. Recommendations from previous research point to the need to have appraisal ratings arrived at from multiple sources that would include the public who are the primary consumers of policing services. Police satisfaction surveys and needs analysis reports have yielded recommendations that the public would provide valuable input in determining the effectiveness of a police officer. Other key players in determining appraisal ratings are the officer’s supervisor and peers with whom they have handled assignments. This research applied the prototyping methodology to design, develop and test a fuzzy expert based appraisal model with multiple appraisal data inputs and a single performance score output. To determine performance scores through a uniform procedure, a fuzzy controller was used to approximate the relationship between inputs and outputs via interpolation. The reason for applying fuzzy logic for the development of the appraisal model lies in the fact that vagueness is expected whenever human decisions are made. The crisp data inputs to the fuzzy controller were obtained from a mobile application developed to capture incident reports in real-time from the public, enable swift response by an officer and enable user rating upon completion of the assignment. Fuzzy logic is effective where multi-criteria decision-making is required such as an appraisal of employee performance. The web application provides an input interface for ratings by supervisors, peers and sub-ordinates as well as administrative tools. This model will enhance objectivity in the appraisal of police officers, which will also enable accurate identification of an individual’s development needs.
A Thesis Submitted to the School of Computing and Engineering Science in partial fulfillment of the requirements for the award of Master of Science in Computing and Information Systems Degree.
Keywords: Performance appraisal model; Police officers; Employees